PROBLEMATIKA KEBIJAKAN PENDIRIAN RUMAH IBADAT DI TENGAH KERAGAMAN INDONESIA - Bandur, Hironimus (SEPAKAT-Jurnal Pastoral Kateketik, 2017)
The house of worship is seen as a small part of the religious entity of Indonesiansociety. But can not hide the fact that the house of worship closed to acontacting area of conflict-prone. The discourses of religious houses of worshipshould be the object of serious discussion until they have a comfortable placein the hearts of all religious communities. It is a phenomenal fact, in whichthe establishment of the house of worship has become an area of competitionfor justice and freedom as well as tolerance among Indonesian religiouscommunities. Governments in cooperation with interfaith leaders continuallystrive to revise the law and policy products governing the religious life of thepeople, in the hope that legal production becomes a tool to connect the factsof Indonesiaâs differences in many things including religion. Therefore, itâsneeded an emancipative, equalitive and inclusive law products. In 2006, thegovernment issued a legal basis for the dissemination of religious houses ofworship in Indonesia, called the âPeraturan Bersama Menteriâ (PBM). Thegovernment proves the presence of the state in the matter of building a houseof worship, through PBM numb. 9 and 8 2006. But it turns out after theimplementation of the PBM, the issue surrounding the establishment of thehouse of worship even increased by almost the same reason that paradigmmajority versus minorities tend to destructive, clash of view to differences andalso even including legal formulation an sich that needs to be revised.